The relationship between task identity, task autonomy and feedback with organizational commitment among employees in Jabatan Ketua Menteri Melaka (JKMM) / Nur Amirah Abdul Ghafar and Nurul Shafika Zulpikri - Abdul Ghafar, Nur Amirah; Zulpikri, Nurul Shafika (Faculty of Business and Management, 2016)
Organizational commitment is one of the major challenges in human resource management and without commitment employees; organization stands to suffer in terms of efficiency and effectiveness. The study aimed to determine the relationship between task identity, task autonomy and feedback with organizational commitment among employees in Jabatan Ketua Menteri Melaka (JKMM) using Hackmans’s Job Characteristics Theory. Hence, the research hypothesis was to examine whether there is significant relationship between task identity, task autonomy and feedback with organizational commitment. The research design used a quantitative approach. Methodology of research used was descriptive statistics, correlations and reliabilities. The dependent variable is organizational commitment and independent variables represent task identity, task autonomy and feedback. A sample of 248 employees was obtained from a population of 730 employees. The population was conveniently approached and primary data was collected using questionnaires. The data collected was edited, coded, and tabulated. It was analyzed using SPSS (statistical package for social scientists) version 20. Findings showed the direction of the relationship between all variables is positive relationship meaning that independent variables have a significant effect on organizational commitment. The study recommends that managers of organizations can use these findings to make human resource decisions regarding job analysis.